(untitled) (Desenvolvimento em Questão, 2026)
This study examines the perceptions of broiler chicken producers in Miraguaí, Rio Grande do Sul (Brazil) regarding the vertical integration system, focusing on contractual, productive, and environmental aspects. Using a qualitative case study with nine producers integrated with Mais Frango Ltda., interviews and document analysis were conducted. Findings highlight benefits such as technical assistance and input supply, but also challenges including contractual rigidity, lack of protection against market fluctuations, and high production costs. Productive factors like animal welfare and proper management directly affect profitability. Greater clarity, flexibility, and incentives for modernisation are needed to enhance sustainability and balance in contractual relations.